EUROPEAN UNION’S GREEN SOFT POWER IN CONTEMPORARY POLITICS: INSTRUMENTS, CONDITIONALITY AND GLOBAL LEADERSHIP - Petronijević, Ognjen; Todorović Lazić, Jelena (Political Review, 2025)
The article examines the concept of green soft power with a focus on the unique example of the European Union (EU). As one of the global leaders in combating climate change, the EU mobilizes its green soft power to shape the environmental changes internationally through non-coercive means. The article recognized environmental diplomacy, global climate leadership, sustainable culture, and green normative framework as key resources in projecting EU green soft power. Using regulatory authority, the EU complements its soft power with conditional mechanisms, making the Union adopt a hybrid form of soft power. The paper argues that the EU combines domestic ecological transformation, exemplified by the European Green Deal, with external instruments such as Chapter 27 of the enlargement process and the Global Gateway initiative, to project environmental norms globally. It further analyzes the EU strategy in recent international climate negotiations (COP26-COP28). Finally, the paper examines two important factors in international relations that limit the EU’s capacity to perform and achieve environmental objectives in the international arena – the problematic withdrawal from the Paris Agreement by the United States, and complex evolving relations with China.